Safety and efficacy of balloon-mounted stent in the treatment of symptomatic intracranial atherosclerotic disease: a multicenter experience. (4th August 2021) - Mohammaden, Mahmoud H; Nogueira, Raul G; Tekle, Wondwossen; Ortega-Gutierrez, Santiago; Farooqui, Mudassir; Zevallos, Cynthia B.; Hanel, Ricardo A; Cortez, Gustavo M; Aghaebrahim, Amin; Starke, Robert M; Aref, Hany; Elbassiouny, Ahmed; et al.
Abstract : Background: Randomized clinical trials have failed to prove that the safety and efficacy of endovascular treatment for symptomatic intracranial atherosclerotic disease (ICAD) is better than that of medical management. A recent study using a self-expandable stent showed acceptable lower rates of periprocedural complications. Objective: To study the safety and efficacy of a balloon-mounted stent (BMS) in the treatment of symptomatic ICAD. Methods: Prospectively maintained databases from 15 neuroendovascular centers between 2010 and 2020 were reviewed. Patients were included if they had severe symptomatic intracranial stenosis in the target artery, medical management had failed, and they underwent intracranial stenting with BMS after 24 hours of the qualifying event. The primary outcome was the occurrence of stroke and mortality within 72 hours after the procedure. Secondary outcomes were the occurrence of stroke, transient ischemic attacks (TIAs), and mortality on long-term follow-up. Results: A total of 232 patients were eligible for the analysis (mean age 62.8 years, 34.1% female). The intracranial stenotic lesions were located in the anterior circulation in 135 (58.2%) cases. Recurrent stroke was the qualifying event in 165 (71.1%) while recurrent TIA was identified in 67 (28.9%) cases. The median (IQR) time from the qualifying event to stenting was 5 (2–20.75) days. Strokes were reported in 13 (5.6%) patients within 72 hours of the procedure; 9 (3.9%) ischemic and 4 (1.7%) hemorrhagic, and mortality in 2 (0.9%) cases. Among 189 patients with median follow-up time 6 (3–14.5) months, 12 (6.3%) had TIA and 7 (3.7%) had strokes. Three patients (1.6%) died from causes not related to stroke. Conclusion: Our study has shown that BMS may be a safe and effective treatment for medically refractory symptomatic ICAD. Additional prospective randomized clinical trials are warranted.